The occurrence and fate of chemicals of emerging concern in coastal urban rivers receiving discharge of treated municipal wastewater effluent. (7th January 2014) - Sengupta, Ashmita; Lyons, J. Michael; Smith, Deborah J.; Drewes, Jörg E.; Snyder, Shane A.; Heil, Ann; Maruya, Keith A.
Abstract To inform future monitoring and assessment of chemicals of emerging concern (CECs) in coastal urban watersheds, the occurrence and fate of more than 60 pharmaceuticals and personal care products (PPCPs), commercial/household chemicals, current‐use pesticides, and hormones were characterized in 2 effluent‐dominated rivers in southern California (USA). Water samples were collected during 2 low‐flow events at locations above and below the discharge points of water reclamation plants (WRPs) and analyzed using gas chromatography–mass spectrometry and liquid chromatography–tandem mass spectrometry. Approximately 50% of targeted CECs were detectable at stations downstream from WRPs, compared with <31% and <10% at the reference stations above the WRPs. Concentrations of chlorinated phosphate flame retardants were highest among the CECs tested, with mean total aggregate concentrations of tris(2‐chloroethyl) phosphate (TCEP), tris(1‐chloro‐2‐propyl) phosphate (TCPP), and tris(1, 3‐dichloro‐2‐propyl) phosphate (TDCPP) of 3400 ng/L and 2400 ng/L for the 2 rivers. Maximum in‐stream concentrations of pyrethroids (bifenthrin and permethrin), diclofenac, and galaxolide exceeded risk‐based thresholds established for monitoring of CECs in effluent‐dominated receiving waters. In contrast, maximum concentrations of PPCPs commonly detected in treated wastewater (e.g., acetaminophen, N, N, diethyl‐meta‐toluamide [DEET], and gemfibrozil) were less than 10% of established thresholds. Attenuation of target CECs was not observed downstream of WRP discharge until dilution by seawater occurred in the tidal zone, partly because of the short hydraulic residence times in these highly channelized systems (<3 d). In addition to confirming CECs for future in‐stream monitoring, these results suggest that conservative mass transport is an important boundary condition for assessment of the input, fate, and effects of CECs in estuaries at the bottom of these watersheds. Environ Toxicol Chem 2014;33:350–358. © 2013 SETAC